The problems of entering the industry of Kyrgyzstan in economic space of the Customs Union - CH. Z. Kaibyldaeva (Путеводитель предпринимателя, 2020)
The article analyzes the prospects and the main factors of competitiveness of the industrial sector and selected industries of the Kyrgyz Republic in terms of joining in the economic space of the Customs Union and the Eurasian economic Union.